Investigating the Impact of Socia Media on Consumer Behavior in Online Fashion Retail: A Focus on Influencer Marketing and Visual Content Strategies - Trimanda Fujiwara; Hernandez Martin (Cebong Journal, 2023)
This research investigates the influence of social media on consumer behavior in the context of purchasing online fashion products. Utilizing a mixed-methods approach, the study combines qualitative in-depth interviews and quantitative online surveys to provide a comprehensive understanding of the intricate relationship between digital platforms and consumer choices in the dynamic landscape of online fashion retail. Key findings reveal that social media platforms, notably Instagram and TikTok, play a pivotal role as primary sources of fashion inspiration for online consumers. Influencers emerge as powerful drivers of consumer purchasing decisions, emphasizing the need for businesses to strategically collaborate with influential figures. Visual content on social media is identified as a significant trigger for impulse buying behaviors, highlighting the importance of a visually appealing content strategy for businesses. The integration of e-commerce features within social media platforms, such as shoppable posts and in-app checkout options, is well-received, indicating a seamless transition from content discovery to the purchasing journey. As ethical and sustainable considerations gain prominence in online fashion purchases, businesses are encouraged to align with evolving consumer values. The implications of these findings extend to businesses, marketers, and policymakers. Strategic social media presence, influencer collaborations, and a compelling visual content strategy are recommended for businesses seeking to capitalize on digital consumer behaviors.